DEVELOPMENT AND VALIDATION OF SIMULTANEOUS ASSAY METHOD FOR DEXTROMETHORPHAN HYDROBROMIDE AND DIPHENHYDRAMINE HYDROCHLORIDE IN SYRUP DOSAGE FORM USING DERIVATIVE ULTRAVIOLET SPECTROPHOTOMETRY - Gery
Derivative spectrophotometry is a method that is fast, cheap, and simple. This method can be used as alternative method of standard method usually using high performance liquid chromatography that relatively long, expensive, and complicated. In this research, derivative spectrophotometry was developed for syrup of the mixture of dextromethorphan hydrobromide and diphenhydramine hydrochloride. Initially, order 0, 1, and 2 spectrums of each dextromethorphan hydrobromide and diphenhydramine hydrochloride were determined in several concentrations. For each analyte, the wavelengths of zero-crossing of analyte and linearity of absorption of other analyte at these wavelengths were determined. Based on the linearity and magnitude of the absorbance, the order and wavelengths were selected for analysis. Validation was done with the parameters of accuracy and precision for simulation sample of syrup. Based on development, assay of these analyte carried in the order 1 ultraviolet spectrum with wavelength for analysis of dextromethorphan hydrobromide was 287.6 nm and for diphenhydramine hydrochloride was 245.2 nm after preservative seperated from the syrup with liquid-liquid extraction in acid condition with ether. For accuracy of this method, % recovery ranged 96-101% within range of requirement. For intraday, %RSD ranged 0-1.2% which within requirement range and for interday precision, %RSD ranged 0.8-3% which within the requirement range. Therefore, this method can be used as an alternative assay method of dextromethorphan hydrobromide and diphenhydramine hydrochloride in the syrup dosage form